Methodological guidance for a practical classes from the course "International cooperation and grantwriting in ecology" - Tykhomyrova, T. S.; Shestopalov, O. V.; Makhonina, O. S. (My University, 2023)
These methodological guidance are intended for practical work and the calculation task from the course "International cooperation and grant writing in ecology". During practical works, students will master team work skills, learn to determine each participant role in team, will get acquainted with the methods of decision-making in the team, will learn how to make up a SWOT analysis for grant application, will master the ability to manage the strategic team development in the process of carrying out professional activities in the ecological area, environmental protection and balanced natural use, will learn how to make an calculation (expenditure budget) for their grant and divide sources of funding. Basic terms in English and their interpretation are also given, which are useful when write in grant applications. In the methodical instructions, the practical classes aims are considered and theoretical material is given. A task realization examples and list of individual tasks are given. The proposed individual tasks are of practical importance and rely on the authors' experience in writing in grant applications.
Keywords: methodological guidance; SWOT analysis; ecological grants; social capital concept; grant budget; environmental area